(untitled) (Minerva, 2019)
This article presents a novel study of the beginning of Don Quixote II,53 as an instance of an ancient literary topos that was often revisited in the Renaissance, namely the antithesis between the eternal cycles of nature and the linearity and brevity of human life. It is argued that Horace, carm. 4,7,9-16 is the main literary model Cervantes followed here. This viewpoint can be further corroborated by demonstrating that Cervantes’s text evokes the commentary on carm. 4,7 provided by J. Villén de Biedma on the poetry by Horace in his Declaración magistral en lengua castellana (Magistral Declaration on Castilian Language, 1599). The discussion further includes previously undetected associations with the Book of Job, along with the possible convergence of this Biblical source with Horace’s poem and with echoes from a passage by Góngora.